2000
DOI: 10.1007/pl00007895
|View full text |Cite
|
Sign up to set email alerts
|

The effect of corticosteroid and cyclosporin A on murine corneal allograft rejection

Abstract: The detection of Th1 cytokines in the cornea but not the serum of mice at the time of allograft rejection is in accordance with the finding of long-lasting dose-dependent immunosuppression of topical steroids and the inefficacy of short-term systemic CsA and corticosteroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
4

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 14 publications
1
10
0
4
Order By: Relevance
“…Both Rapa and CsA have been studied independently as immunosuppressive agents in experimental keratoplasty [26,27]. A consistent beneficial effect of Rapa monotherapy in corneal allograft survival has been previously reported [12,27].…”
Section: Discussionmentioning
confidence: 74%
“…Both Rapa and CsA have been studied independently as immunosuppressive agents in experimental keratoplasty [26,27]. A consistent beneficial effect of Rapa monotherapy in corneal allograft survival has been previously reported [12,27].…”
Section: Discussionmentioning
confidence: 74%
“…Similar findings were reported using "conventional" prednisolone treatment in an experimental keratoplasty model. All corneal grafts remained clear during a treatment course of 80 days but subsequently were rejected following cessation of steroid eye drop application [18]. Interestingly, the same study revealed that topical steroid treatment was even superior to systemic treatment, probably indicating that local immunoregulatory events play a dominant role in corneal graft rejection.…”
Section: Discussionmentioning
confidence: 92%
“…These cells may migrate from the iris via the uveoscleral pathway and reach the regional lymph nodes, whereupon they stimulate clonal expansion of antigen-specific T cells. It has previously been shown that IFN-γ positive cells are present in corneal grafts 2 weeks and 4 weeks after allogeneic transplantation [18,24]. This could represent a reaction to the antigen presented to the immune system by the antigen-presenting cells such as the above-mentioned macrophages.…”
Section: Figmentioning
confidence: 97%